THE EFFECT OF WORK ENVIRONMENT AND WORK LOAD ON NURSES’ MOTIVATION IN BHAYANGKARA SESPIMMA POLRI HOSPITAL, SOUTH JAKARTA IN 2018 - Yeni Febrianti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The hospital is one of the health service facilities that provides health services that are promotive, preventive, curative, and rehabilitative to the community. Health services must continue to be improved, so that nurses' motivation can be maintained properly. To be able to directly support nurses' motivation, a conducive work environment and a suitable workload are needed. Nurses as professional staff are responsible and authorized to provide nursing services independently, and collaborate with other health workers in accordance with their authority, especially related to the practice environment and the authority of nurses. Nurses' complaints of high workload conditions and lack of appreciation for their work, sometimes triggers a lack of motivation at work, resulting in low levels of optimal performance achievement. The objectives of this study are: (1) To analyze the effect of the work environment on nurses' motivation. (2) To analyze the effect of workload on nurse motivation. (3) To analyze the effect of the work environment and workload together on nurse motivation. The results of this study concluded that the work environment (X1) and workload (X2) had a positive and significant effect on the motivation of nurses (Y) of the Bhayangkara Sespimma Polri Hospital in South Jakarta. The better the work environment and workload, the better the motivation of nurses, and vice versa. Keywords: work environment, workload, motivation, nurse